COMPLICATIONS AIGUËS METABOLIQUES DU DIABETE SUCRE DANS L’UNITE DE REANIMATION DE L’HOPITAL UNIVERSITAIRE DE PARAKOU (BENIN) - Tchaou, Blaise Adelin; Gomina, Moutawakilou; Agbo, Alex Homère Mayeul; Akpona, Simon Ayélèroun (European Scientific Journal, ESJ, 2014)
Objective: To evaluate the management of acute metabolic complications of diabetes mellitus in the intensive care unit of the university hospital of Parakou. Patients and methods: This was a descriptive and analytical cross-sectional study with a prospective data collection conducted over 10 months (December 1st, 2011 to September 30th, 2012). It involved 43 patients. Results: The admission of the acute complications of diabetes metabolic rate was 7.8%. The mean age of patients was 57.7 ± 13 years with a female predominance (55.8%). The main reasons for admission were: coma (69.8%), intense asthenia (18.6%) and trauma 7.0%. Poor adherence to treatment was observed in 60.6% of known diabetic patients. Acute metabolic complications were objectified: the Hyperosmolar hyperglycemia syndrome (41.9%), hypoglycemia (30.2%) and ketoacidosis (27.9%). The occurrence of complications was associated with advanced age (p = 0.01), low socioeconomic status (p = 0.00), the late consultation period (p = 0.00) and high plasma osmolality (p = 0.00). Lethality 14%, was related to advanced age (p = 0.02), long consultation period (p = 0, 02) and signs of severity (Fisher exact = 0.03). Conclusion: This study on the acute complications of diabetes mellitus in Parakou shows that this clinical situation is a real concern. Awareness and education of diabetes to better manage and improve the means of support in the intensive care unit help reducing death rates and the deleterious effects of acute metabolic complications of diabetes mellitus.